Social Media Slang Evolution in Indonesia: A Big Data Analysis of Instagram and TikTok Hashtags (2018-2024) - Siti Aisyah Nurhidayah (Journal of Linguistics and Communication Studies, 2025)
The evolution of social media slang in Indonesia reflects broader shifts in digital communication, cultural identity, and linguistic adaptation. This study analyzes the emergence, adoption, and transformation of slang terms on Instagram and TikTok from 2018 to 2024, using big data techniques, Natural Language Processing (NLP), and sentiment analysis. By examining trending hashtags, user interactions, and slang co-occurrence networks, this research provides insights into how digital expressions gain traction, change in meaning, and influence mainstream communication. Findings reveal that platform-specific dynamics shape slang longevity and usage patterns. Instagram fosters longer-lasting slang adoption due to its text-based interactions, while TikTok accelerates slang virality but shortens its lifecycle due to its algorithm-driven content discovery. The study also highlights the sociolinguistic drivers of slang formation, including regional dialects, phonetic modifications, meme culture, and generational preferences. Sentiment analysis indicates that while some slang terms maintain positive or neutral meanings, others develop controversial connotations over time, raising ethical concerns regarding misinformation, slang normalization, and algorithmic amplification. These findings have important implications for language policy, digital branding, and political discourse. As slang continues to influence marketing strategies, activism, and online engagement, policymakers must consider the balance between linguistic innovation and the preservation of formal language standards. The study suggests that future research should explore AI-driven slang prediction models, digital education strategies, and the long-term impact of slang integration into mainstream Indonesian language.